Dynamic behavior of fiber reinforced composite slab induced by human walking - Soufeiani, Leila (2013)
Composite floor systems are being increasingly used in building and footbridge constructions, as they are economical and easy to construct. These composite floor systems use high strength material to achieve longer spans and are thus slender. As a result, they are vulnerable to vibration induced under service loads. Resonance of such structure is one of the most critical problems which without considering dynamic aspects in design, may lead to unsafe and discomfort circumstances for the users. The purpose of this study is to provide an appropriate analysis methodology through finite element analysis to assess the dynamic responses of composite slab and corresponding human comfort problems. A linear elastic finite element analysis through consideration of walking load model (applied in mid-span) with respect to application of different percentages of ply orientation and stacking sequences of FRP laminate in slab is conducted. Variation in material properties for each case and damping ratio is established separately to capture the maximum responses in terms of deflection and accelerations. The dynamic responses of deflection and accelerations are compared with the serviceability deflection limits and human comfort levels (of acceleration) to assess these floor types